Pencegahan Penyalahgunaan Senjata Api Dalam Pelaksanaan Tugas Prajurit TNI - Arief Fahmi Lubis (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2021)
In carrying out its duties, the TNI is given the authority to use firearms in accordance with existing military equipment standards. The TNI limits the use of firearms to prevent misuse, namely in peaceful or non-combat conditions. The aim of this research is to show that every member of the TNI actually has the same position as ordinary people who are not members of the military, but as members of the TNI apart from being subject to the legal rules that apply in society. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description at the time of the research. The results of this research show that the aim of implementing licensing, supervision and control of military standard firearms is to create a management system that is well structured and correct according to procedures and can be accounted for, so that there is no misuse of firearms and/or ammunition.